“What’s in a name?” Bairdia fasciata Brady, 1870, and two new Caribbean species of Bairdoppilata (Bairdiidae, Podocopida, Ostracoda) - Maddocks, Rosalie F.; Horne, David J. (Zootaxa, 2024)
The single specimen of Bairdia fasciata Brady, 1870 in the Great North Museum, Newcastle upon Tyne, UK, is declared to be the holotype by monotypy. Because it is a closed carapace, the internal characters remain unknown. Taxonomically, neither the genus nor the species is identifiable, nor can the subsequent identification in Belize be confirmed. New sampling at the type locality in the Cape Verde Islands is recommended, to recover a population for taxonomic re-description. Here, two new species of Genus Bairdoppilata are described from the carbonate platform of Belize, Ba. magnafasciata, n. sp. and Ba. parvafasciata, n. sp. Both display similarities to B. fasciata from the Cape Verde Islands, but neither one can be identified with that species. Both species are widely distributed in shallow coastal assemblages around the central and northern Caribbean. In taxonomy, names matter, and the correction of published misidentifications is essential. Clarification of these species enables more accurate delineation of ecological and biogeographical distributions in Caribbean assemblages.